Activated carbons from biocollagenic wastes of the leather industry for mercury capture in oxy-combustion. (15th February 2015) - Lopez-Anton, M.A.; Gil, R.R.; Fuente, E.; Díaz-Somoano, M.; Martínez-Tarazona, M.R.; Ruiz, B.
Highlights: Activated carbons obtained from leather industry waste may retain mercury. Different mercury behavior was observed in oxygen and oxy-combustion atmospheres. Mercury retention capacity of activated carbons decreased in presence of acid gases. High percentage of mercury oxidation was produced in an oxy-combustion atmosphere. Abstract: This study evaluates the capacity of a series of activated carbons obtained from leather industry waste to retain mercury. The behavior of these materials was compared in two simulated flue gas compositions at laboratory scale. The atmospheres were (i) a typical coal oxy-fuel combustion atmosphere and (ii) an O2  + N2 atmosphere. The activated carbons displayed different behaviors depending on their characteristics and the gas composition. The best results were obtained for the activated carbon with the highest surface area and greatest amount of micropores, sulfur and acidity character, these results being comparable to those of an activated carbon impregnated with sulfur specifically designed for capturing elemental mercury. The highest level of mercury retention was achieved in a O2  + N2 atmosphere. However, independently of the ability of these materials to capture mercury, their most interesting characteristic was their ability to oxidize mercury in an oxy-combustion atmosphere, since this would facilitate the retention of mercury in flue gas desulfurization units with the consequence that the risk of damage to the CO2 compression and purification units would be reduced or even removed.